2019
DOI: 10.3390/risks7040124
|View full text |Cite
|
Sign up to set email alerts
|

Social Security Benefit Valuation, Risk, and Optimal Retirement

Abstract: We develop valuation and risk techniques for the future benefits of a retiree who participates in the American Social Security program based on their chosen date of retirement, the term structure of interest rates, and forecasted life expectancy. These valuation methods are then used to determine the optimal retirement time of a beneficiary given a specific wage history and health profile in the sense of maximizing the present value of cash flows received during retirement years. We then examine how a number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Besides, modern studies of economic relations in pension systems suggested an original approach of social comparison for the purposes of stimulating saving behaviour in order to increase future savings (Raue, D'Ambrosio & Coughlin, 2020); developed a set of scientific methods and tools for mitigating risks of investing in pension assets (Ali, Fang, Sota, Taylor, & Wang, 2019;McDonald, 2019;Weiss-Cohen, Ayton, & Clacher, 2020), and indentified cause-and-effect relations of falling living standards at retirement (Allais, Leroy, & Mink, 2020;Chen, 2019;Hammer et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, modern studies of economic relations in pension systems suggested an original approach of social comparison for the purposes of stimulating saving behaviour in order to increase future savings (Raue, D'Ambrosio & Coughlin, 2020); developed a set of scientific methods and tools for mitigating risks of investing in pension assets (Ali, Fang, Sota, Taylor, & Wang, 2019;McDonald, 2019;Weiss-Cohen, Ayton, & Clacher, 2020), and indentified cause-and-effect relations of falling living standards at retirement (Allais, Leroy, & Mink, 2020;Chen, 2019;Hammer et al, 2020).…”
Section: Introductionmentioning
confidence: 99%